2018
DOI: 10.3390/su10072285
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment and Parking Availability: Impacts on Car Ownership and Use

Abstract: Along with urbanization and economic development, the number of private cars has increased rapidly in recent years in China, which contributes to concerns about traffic congestion, hard parking, energy consumption, and emissions. This study aims to investigate the joint effect of built environment and parking availability on car ownership and use based on a household travel survey conducted in Changchun, China. The binary logistic model was first employed to investigate the determinants of the car ownership in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…This may be explained by that hukou system ensure that households with local hukou enjoy better social welfares in China. Additionally, the results reveal that higher household income increases the likelihood of owning cars, which is consistent with existing studies [ 1 , 56 , 57 ]. Because many Chinese families still cannot afford to purchase a car [ 26 ], household income still serves as one of the primary determinants of household car ownership.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This may be explained by that hukou system ensure that households with local hukou enjoy better social welfares in China. Additionally, the results reveal that higher household income increases the likelihood of owning cars, which is consistent with existing studies [ 1 , 56 , 57 ]. Because many Chinese families still cannot afford to purchase a car [ 26 ], household income still serves as one of the primary determinants of household car ownership.…”
Section: Resultssupporting
confidence: 91%
“…Distance to CBD shows no significant influence on car ownership, which is different from the existing study [ 34 ]. However, the existing studies also produce mixed results about the influence [ 31 , 34 , 57 ]. On one hand, living farther from CBD means a longer commuting distance due to the fact that most employments concentrate around CBD.…”
Section: Resultsmentioning
confidence: 99%
“…On a closely related note, we found that where the number of parking facilities increased, the probability of AST rapidly decreased and other research has suggested that parking availability in Asia is associated with more car trips (Yin, Shao, and Wang 2018). The authors of this study also suggested that implementing parking restrictions at journey origins and destinations could encourage more sustainable travel, while our study goes one-step further in suggesting that this could also promote more travel that is active through discouraging car use (Yin, Shao, and Wang 2018).…”
Section: Discussionsupporting
confidence: 66%
“…We found TDB to be positively related to car ownership (cars per person), which was our proxy for car congestion (Table 2). Traffic congestion arises near more populated areas where the car ownership index is higher [39,40]. BSS services are the alternative for car trips, especially in urbanised areas where the travel time loss caused by congestion is significant.…”
Section: Regression Analysis Of the Factors Influencing Bss Performancementioning
confidence: 99%